Eric Voegelin and the Schelling Renaissance: The Schellingian orientation in Voegelin's later works (1952--1985) - Day, Gerald L. (My University, 2000)
This dissertation compares the philosophy of Friedrich Wilhelm Joseph von Schelling (1775-1854) and Eric Voegelin (1901-1985). More specifically, it discusses the considerable extent to which Voegelin drew upon Schelling in the formulation of his mature philosophy of consciousness and its supporting historiography. There are three parts to the presentation of my argument. First, I consider why Voegelin's published references to Schelling varied greatly throughout the course of his career. Secondly, I consider the earliest of Voegelin's major works, examining the extent to which they draw upon Schelling's. Initially, Voegelin thought of Schelling as a philosopher who managed to transcend the intellectual extremes of his time--idealism and nihilism--and Voegelin attempted to follow his example. Finally, I discuss how Voegelin distributed aspects of Schelling's post-idealist thought in his own mature works on the philosophy of consciousness and its progressive differentiation in history. I conclude by offering a number of critical reflections on Voegelin's Schellingian view of history as a theogonic process of being itself which tends toward the "immortalizing" transfiguration of humanity
Keywords: Religion; Religion